Cognitive behaviors in Indonesian-English translation: Exploring translation processes - Andi Rustandi (JALL (Journal of Applied Linguistics and Literacy), 2023)
This present study investigated the cognitive behaviors in the processes of Indonesian-English translation. Two research questions were employed to find out; 1) what types of cognitive behaviors emerge in the translation processes, 2) and which types of cognitive behavior are the most dominant in the translation process? The data were taken from screen recording of translator activities in video supplemented by think-aloud protocols in TransCon6_ID.mp4 entitled "Panorama Sumba." The data were analysed qualitatively by following the steps: transcribing, identifying, classifying, and interpreting (Bailey, 2008). The result reveals that the translator uses several cognitive behaviors such as generating ideas, revising, elaborating, clarifying, retrieving, rehearsing, referencing or resourcing, and summarizing. However, the translator's most dominant behavior is referencing by seeking the dictionaries to solve the translation problem.